Silent partners in multicultural education - Itkonen, Tuija; Dervin, Fred, 1974- (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
This volume aims to stimulate interest in the under-researched role of silent partners (SPs) in multicultural education. Silent partners include formal and informal places-spaces in schools (e.g. architecture, classroom facilities, libraries, corridors, playgrounds, canteens), objects (e.g. teaching aids, furniture, wall decorations and overall interior design), interactive technologies (use of devices and applications) but also often taken-for-granted and not immediately visible patterns of thought, ideologies and assumptions.People involved in education all engage and work with a number of SPs that contribute to the delivery of curricula, but also to social life and well-being in and out of schools. The way places-spaces, objects and technologies influence the school community's experiences of learning, well-being and social justice is rarely observed and problematised in education - hence the adjective 'silent' in the term 'silent partners'.This book not only fills a significant empirical gap, but it can also inject public debate over future working environments in schools for multicultural education. It will be relevant to both researchers interested in developing their knowledge on these issues from a different perspective but also educators in search of inspiration for multicultural education.
Keywords: Multicultural education.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; elektronické knihy; electronic books